Karakteristik Penyakit Compound Miop Astigmat di Klinik Mata JEC Orbita Makassar Periode 2022.4-2024.4 - Usman, Adinda Zahra; Nurmadilla, Nesyana; Novriansyah, Zulfikri Khalil; Amir, Suliati P.; Maharani, Ratih Natasha (Universitas Batanghari Jambi, 2025)
This study aimed to determine the characteristics of compound myop astigmatism disease at the JEC Orbita Makassar Eye Clinic. The design of this study was cross-sectional and samples were taken from medical record for the period April 2022.4 – 2024.4. The results showed that the majority of compound myop astigmatism sufferers were women of productive age between 17 and 25 years and were students and housewives (IRT). Prolonged screen exposure (computer vision syndrome) is the most likely risk factor for compound myopic astigmatism suffered by patients.